Furniture and regenerative design: Befriend sustainability - Ing. arch. Katarína Lauková Zajíčková (Slovak University of Technology, Faculty of Architecture and Design, 2020)
This article focuses on item recycling and its related aspects in the context of sustaina-bility. It defines the term based on the extent of interfering with the original object and draws the points of intersection in the context of sustainability, such as selection of materials and their combination, as well as their processing or treatment. In the light of the aforesaid, it shows that the cradle to cradle system is pretty much applicable and, along with other principles it also becomes an integral part of environmentally responsi-ble design with respect to item recycling. In addition to the sustainability context, the item recycling also has an inherent potential to follow up on the cultural memory (in particular in using local resources), to encourage and promote the revival of or return to trades and crafts related to partial repairs or surface renovations, and to express the value associated with the cultural memory. These values, coupled with the challenge posed by open design, present new possibilities for the product development and distri-bution and allow for design verification through the process of prototype refinement among craftsmen—designers, even with the outcome in the form of a new type of “serial design”. The user becomes an active player in the process and due to being involved through the handiwork develops a relationship with the product: this further increases the probability that the product will be used longer and its lifetime will be considerably prolonged. This leads back to the concept of sustainability, which be-comes its integral part.